Pattern Recognition c - Palaiahnakote, Shivakumara; Sanniti di Baja, Gabriella; Wang, Liang; Yan, Wei Qi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This two-volume set constitutes the proceedings of the 5th Asian Conference on ACPR 2019, held in Auckland, New Zealand, in November 2019. The 9 full papers presented in this volume were carefully reviewed and selected from 14 submissions. They cover topics such as: classification; action and video and motion; object detection and anomaly detection; segmentation, grouping and shape; face and body and biometrics; adversarial learning and networks; computational photography; learning theory and optimization; applications, medical and robotics; computer vision and robot vision; pattern recognition and machine learning; multi-media and signal processing and interaction.
Keywords: Pattern recognition systems; Image processing -- Digital techniques; Computer vision; Machine learning; Computers; Application software; Automated Pattern Recognition; Computer Imaging, Vision, Pattern Recognition and Graphics; Machine Learning; Computing Milieux; Computer and Information Systems Applications